High temperature performances of normally-off p-GaN gate AlGaN/GaN HEMTs on SiC and Si substrates for power applications. Issue 9 (August 2015) - Fleury, Clément; Capriotti, Mattia; Rigato, Matteo; Hilt, Oliver; Würfl, Joachim; Derluyn, Joff; Steinhauer, Stephan; Köck, Anton; Strasser, Gottfried; Pogany, Dionyz
Abstract: We analyse high temperature effects (up to 420 °C) in the performances of p-GaN gate normally-off AlGaN/GaN HEMTs on Si and SiC substrates for power applications. With increasing temperature, IDMAX (RON ) decreases (increases) and the threshold voltage slightly decreases independently of the substrate and doping. The room temperature (RT) DC IV characteristics of the devices after 90 min at temperatures above 300 °C are not affected. Step stress experiments at 420 °C show more than twofold decrease of the blocking capabilities compared to RT. Finally, thermal activation of the vertical leakage current has been analysed up to 180 °C. Highlights: p-GaN Gate AlGaN/GaN HEMTs measured in DC up to 420 °C without permanent degradation Decrease of maximum drain current and threshold voltage with temperature above 200 °C Step stress experiments show twofold decrease of blocking capabilities at 420 °C compared to RT. Vertical breakdown is critical or off state leakage and degradation at high temperature.